THE INFLUENCE OF CYBERLOAFING, SELF EFFICACY, AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF EMPLOYEES AT REGIONAL REVENUE AGENCY, BANYUMAS DISTRICT - Fatmah Bagis; Nadila Nuraning; Suyoto Suyoto; Mastur Mujib Ikhsani; Akhmad Darmawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study was to analyze the effect of cyberloafing, self-efficacy and organizational culture on the performance of Kanyumas Regency Regional Revenue Agency employees. Sampling used a purposive sampling method with the criteria of Civil Servants (PNS) distributed using a questionnaire. The sample used was 107 employees. Multiple linear regression analysis was used in this study. The results of this study indicate that cyberloafing has a negative and insignificant effect on employee performance, self-efficacy partially has a negative and insignificant effect on employee performance and organizational culture partially has a positive and significant effect on employee performance. The R2 adjusted coefficient of determination test results was 32.7%. Keywords: Cyberloafing, Self Efficacy and Organizational Culture